Non-pharmacological prevention of postoperative delirium by occupational therapy teams: A randomized clinical trial - Alvarez, Evelyn A.; Rojas, Veronica A.; Caipo, Lorena I.; Galaz, Melany M.; Ponce, Daniela P.; Gutierrez, Rodrigo G.; Salech, Felipe; Tobar, Eduardo; Reyes, Fernando I.; Vergara, Rodrigo C.; Egaña, Jose I.; Briceño, Constanza A.; et al. (Frontiers in Medicine, 2023)
Background Patients who develop postoperative delirium (POD) have several clinical complications, such as increased morbidity, increased hospital stays, higher hospital costs, cognitive and functional impairment, and higher mortality. POD is a clinical condition preventable by standard non-pharmacological measures An intensive Occupational Therapy (OT) intervention has been shown to be highly effective in preventing delirium in critically ill medical patients, but it is unknown the effect in surgical patients. Thus, we designed a prospective clinical study with the aim to determine whether patients undergoing intervention by the OT team have a lower incidence of POD compared to the group treated only with standard measures. Methods A multicenter, single-blind, randomized clinical trial was conducted between October 2018 and April 2021, in Santiago of Chile, at a university hospital and at a public hospital. Patients older than 75 years undergoing elective major surgery were eligible for the trial inclusion. Patients with cognitive impairment, severe communication disorder and cultural language limitation, delirium at admission or before surgery, and enrolled in another study were excluded. The intervention consisted of OT therapy twice a day plus standard internationally recommended non-pharmacological prevention intervention during 5 days after surgery. Our primary outcome was development of delirium and postoperative subsyndromal delirium. Results In total 160 patients were studied. In the interventional group, treated with an intensive prevention by OT, nine patients (12.9%) developed delirium after surgery and in the control group four patients (5.5%) [p = 0.125, RR 2.34 CI 95 (0.75–7.27)]. Whereas subsyndromal POD was present in 38 patients in the control group (52.1%) and in 34 (48.6%) in the intervention group [p = 0.4, RR 0.93 CI95 (0.67–1.29)]. A post hoc analysis determined that the patient’s comorbidity and cognitive status prior to hospitalization were the main risk factors to develop delirium after surgery. Discussion Patients undergoing intervention by the OT team did not have a lower incidence of POD compared to the group treated only with standard non-pharmacological measures in adults older than 75 years who went for major surgery. Clinical trial registration www.ClinicalTrials.gov, identifier NCT03704090.